IMPLEMENTASI NILAI-NILAI DASA DHARMA PRAMUKA SEBAGAI UPAYA PENGUATAN AKHLAKUL KARIMAH PESERTA DIDIK - Moch. Tohet; Anis Fatonah (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the implementation of Dasa Dharma Pramuka values as an effort to strengthen the moral character of students at Nurul Jadid Paiton Junior High School Probolinggo. The research problem departs from the discovery of student behavior that does not fully reflect moral values, such as low discipline, lack of manners, responsibility, and moral awareness in daily life, even though schools have implemented Scouting activities as a mandatory extracurricular. This research uses a qualitative approach with a case study type. Data collection techniques were carried out through observation, in-depth interviews, and documentation, with the principal informants, Islamic Religious Education teachers, Scout coaches, and students. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that the values of Dasa Dharma Pramuka have been systematically implemented through routine scouting activities, habituation, and example of coaches. Practical values such as religiosity, social concern, cooperation, and skills are relatively easy to internalize by students. Meanwhile, values that demand self-control and personal awareness, such as discipline, responsibility, and politeness, still require continuous strengthening and coaching. Overall, the implementation of Dasa Dharma Pramuka values contributes positively to strengthening the moral character of students, but its effectiveness is greatly influenced by the consistency of habituation, the example of coaches, and the support of the school environment